Workshop Penyusunan Evaluasi Pembelajaran menggunakan Artificial Intelligence (AI) di SMK Kesehatan Pelita Bangsa - Kusumaningrum, Betty; Wijayanto, Zainnur; Pardimin, Pardimin; Riyanita Sarani, Fajar; Azis Muhaimin, Nur; Salma Azizah, Salma (Universitas Tunas Pembangunan Surakarta, 2025)
The use of artificial intelligence (AI) technology has resulted in fundamental changes in various aspects of human life, including in the field of education. However, the ability to utilize AI technology has not been widely mastered by teachers and educators. The workshop